Chemical Vapor Deposition of 3C-SiC on [100] Oriented Silicon at low Temperature < 1200°C for Photonic Applications - Kollmuß, Manuel; Köhler, Johannes; Ou, H.; Fan, W.; Chaussende, D.; Hock, Rainer; Wellmann, Peter (Materials Science Forum, 2022)
3C-SiC films have been grown on [100] n-doped Si substrates in a horizontal cold wall CVD reactor. Without the use of plasma enhancement, the precursors silane and propane are used to deposit silicon carbide films at T < 1200°C. The structure of the grown films has been investigated via FESEM, XRD and Raman spectroscopy. It has been found that the growth rates are between 200 and 300 nm/h. Additionally, structural analysis give evidence of polycrystalline phases. Reasons for that could be insufficient cracking of the precursors and homogenous nucleation of Si species in the gas phase.
CRIS-Team Scopus Importer:2022-12-16
Keywords: 3C-SiC; cold wall reactor; CVD; heteroepitaxy; low temperature; void